FORMATION OF PROFESSIONAL COMPETENCE FUTURE FOREIGN LANGUAGE TEACHER AS PEDAGOGICAL PROBLEM - O.I. Dorogaytsev (Academy of Cognitive and Natural Sciences, 2002)
The article deals with the problem of the formation of the professional competence of a future foreign language teacher. The essence of the notion of "professional competence of a future foreign language teacher " and its structure has been revealed. Pedagogical conditions which are to be created to form the professional competence of a future foreign language teacher, have been determined.